Pre-service Teachers’ Beliefs about the Role of Motivation in Language Learning - Jiménez Fajardo, Scarlett Sophia; Dos Santos, Jardel Coutinho (Arandu UTIC, 2025)
This study examines pre-service teachers’ beliefs about motivation in learning English as a foreign language. A mixed-method approach was used to collect data through surveys, interviews, visual narratives, and classroom observations at a public university in Ecuador. Findings reveal that both intrinsic and extrinsic motivation significantly impact the learning process. Intrinsic motivation, driven by personal interest and satisfaction, fosters student autonomy and engagement, encouraging students to take responsibility for their learning. On the other hand, extrinsic factors, such as career opportunities, academic success, and external recognition, reinforce commitment and perseverance. Additionally, pre-service teachers acknowledge their key role in stimulating motivation through interactive strategies, positive feedback, and technology integration. They also recognize the need to create an inclusive and supportive learning environment that fosters students’ confidence and reduces anxiety. This study highlights the importance of motivation in English language teaching and suggests that teacher education programs should provide effective tools to enhance motivation and engagement in the classroom.